Separate and mutual effects of BIRB796 and bortezomib on pHsp27 and viability of U87MG glioma cells - Biltekin, Sevde Nur; Önay Uçar, Evren (Pleiades Publishing, 2023)
Hsp27 phosphorylation is associated with many pathways in glioma, such as tumor cell proliferation and apoptosis inhibition. The aim of this study is to examine the separate and mutual effects of BIRB796 and bortezomib on pHsp27 and to investigate their effects on the viability of U87MG glioma cells. At the same time, the effects of the agents on the p38MAPK enzyme and caspase 3, which plays a role in the mechanism of apoptosis, were also investigated. The cytotoxic effect of bortezomib and BIRB796 on U87MG cells was investigated by MTT method. Hsp27 and pHsp27 proteins expression levels were exhibited by Western Blot analysis. Also, we examined the effects of BIRB796 on p38MAPK (& alpha;, & beta;) enzyme inhibition and caspase 3 activity. According to the MTT results, BIRB796 did not significantly reduce cell proliferation in a dose-dependent manner, but bortezomib significantly reduced it in a dose and time-dependent manner. In Western blot analyses, 5 nM bortezomib, and 100, 250, 500 nM BIRB796 concentrations that show neither a cytotoxic nor a proliferative effect on the cells were used as combined treatment. It was seen that 5 nM bortezomib treatment significantly induced pHsp27 (76%) and Hsp27 (48%) expression levels in the glioma cells. Also it was found that BIRB796 treatments significantly decreased the level of Hsp27 and pHsp27. The combined treatments significantly reduced pHsp27 expression level. Our results showed that all treatments also significantly increased caspase 3 activation. In addition, BIRB796 inhibited p38 & alpha; and p38 & beta; activities depending on time, and this agent effect on p38 & alpha; was stronger than p38 & beta;. All results indicate that BIRB796 and bortezomib have additive effects on cell viability and caspase 3. Also BIRB796 agent may be an effective therapeutic option in cancer cells by reducing cell resistance, apoptosis and pHsp27 expression in the treatment of brain cancer.
Keywords: BIRB796; Bortezomib; pHsp27; Caspase 3; p38MAPK